Respuesta :
x/(2x + 1) + 1/4 = 2/(2x + 1)...multiply all terms by 2x + 1 and cancel out
x + (2x + 1)/4 = 2
3/2x + 1/4 = 2
3/2x = 2 - 1/4
3/2x = 8/4 - 1/4
3/2x = 7/4
x = 7/4 * 2/3
x = 14/12 = 7/6 <==
x + (2x + 1)/4 = 2
3/2x + 1/4 = 2
3/2x = 2 - 1/4
3/2x = 8/4 - 1/4
3/2x = 7/4
x = 7/4 * 2/3
x = 14/12 = 7/6 <==
Answer: Option (D) is the correct answer.
Step-by-step explanation:
The given equation is as follows.
[tex]\frac{x}{(2x+1)} + \frac{1}{4} = \frac{2}{(2x+1)}[/tex]
Taking L.C.D simplify the equation as follows.
[tex]\frac{x(4)+1(2x+1))}{4(2x+1)} = \frac{2}{(2x+1)}[/tex]
Cancelling (2x+1) from both sides, the equation will become as follows.
[tex]\frac{x(4)+1(2x+1))}{4}[/tex] = 2
4x + 2x + 1 = 8
6x + 1 = 8
6x = 7
x = [tex]\frac{7}{6}[/tex]
Thus, we can conclude that x = [tex]\frac{7}{6}[/tex] is the solution for rational equation [tex]\frac{x}{(2x+1)} + \frac{1}{4} = \frac{2}{(2x+1)}[/tex].